Answer :

Given sinx + cosx = m


We have to prove that


Proof:


LHS = sin6x + cos6x


= (sin2x)3 + (cos2x)3


We know that a3 + b3 = (a + b) (a2 + b2- ab)


= (sin2x + cos2x)3 – 3sin2x cos2x(sin2x + cos2x)


= 1 – 3 sin2x cos2x


RHS






= 1 – 3 sin2x cos2x


LHS = RHS


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the values oRD Sharma - Mathematics

Prove that :
<
RD Sharma - Mathematics

The value of sin Mathematics - Exemplar

The value of <spaMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

Fill in the blankMathematics - Exemplar

Fill in the blankMathematics - Exemplar

If 12 sin x – 9 sRD Sharma - Mathematics

Write the intervaRD Sharma - Mathematics